2017
DOI: 10.1007/s11064-017-2328-3
|View full text |Cite
|
Sign up to set email alerts
|

l-3-n-Butylphthalide Activates Akt/mTOR Signaling, Inhibits Neuronal Apoptosis and Autophagy and Improves Cognitive Impairment in Mice with Repeated Cerebral Ischemia–Reperfusion Injury

Abstract: L-3-n-Butylphthalide (L-NBP) exerts neuroprotective effects in animal models of cerebral ischemia, but its potential benefits in repeated cerebral ischemia-reperfusion (RCIR) injury remain unknown. We investigated the effect of L-NBP on cognitive impairment induced by RCIR in mice. Male C57Bl/6 mice received sham surgery or bilateral common carotid artery occlusion (3 times, 20 min each) and were orally administered preoperative L-NBP (30 mg/kg/day, 7 days), postoperative L-NBP (30 or 60 mg/kg/day, 28 days) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 53 publications
2
44
0
Order By: Relevance
“…Some Chinese scholars (Wang, Ma, et al, ) have summarized the research progress of NBP in the treatment of ischemic stroke in the past 20 years, and it was considered as a promising drug for ischemic stroke. A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some Chinese scholars (Wang, Ma, et al, ) have summarized the research progress of NBP in the treatment of ischemic stroke in the past 20 years, and it was considered as a promising drug for ischemic stroke. A large number of experiments at home and abroad have revealed that NBP can regulate brain energy metabolism (Yan, Wang, Yao, Liu, & Xiao, ), protect the mitochondria (Min et al, ), promote normal blood flow in the ischemic area (Xu et al, ), inhibit oxidative stress and platelet aggregation (Li et al, ; Zhao, Li, Zhang, Chen, & Li, ), and prevent the vigorous apoptosis of cells (Min et al, ). In addition, Chinese scholars found that NBP plays a neuroprotective role by acting on multiple active targets (Wang et al, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…L-NBP is a clinically approved drug for treating ischaemic stroke in China (Abdoulaye and Guo, 2016). In cerebral ischemia, L-NBP improved neurological functions and reduced brain injuries in mice with repeated cerebral ischaemia/reperfusion by activating Akt/mTOR signalling resulting in inhibition of neuronal apoptosis and autophagy (Xu et al, 2017).…”
Section: L-3-n-butylphthalide (L-nbp)mentioning
confidence: 96%
“…NBP,as an emerging anti-ischemic drug,inhibits platelet aggregation,reduces thrombosis,improves microcirculation,reduces cerebral infarction volume,resists oxidative stress,protects mitochondrial function,reduces neuronal apoptosis,and reduces in ammation,response and mediate autophagy of neurons,promote neurogenesis,etc in stroke animal models.It exerts multitargeting effects on a variety of pathophysiological mechanisms and shows obvious neuroprotective effects [7][8][9][10][11][12][13][14][15][16][17][18][19][20] .It has been found that its bene cial effect is far beyond the therapeutic scope of stroke [21,22] after further research and application of its application.Especially in the eld of neurodegenerative diseases,people have found that NBP and its derivatives are used in AD,VD,Parkinson's disease (PD) and Amyotrophic Lateral Sclerosis (ALS) all have unique effects and e cacy [7,[23][24][25] .…”
Section: Introductionmentioning
confidence: 99%